2020
DOI: 10.1002/mame.202000383
|View full text |Cite
|
Sign up to set email alerts
|

Desalination of Seawater Using Cationic Poly(acrylamide) Hydrogels and Mechanical Forces for Separation

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/mame.202000383. 2−) drastically decrease the swelling capacity of previously employed anionic poly(acrylic acid-co-sodium acrylate) hydrogels, whereas no influence on the swelling behavior of the synthesized cationic hydrogels is found. The swelling behavior and mechanical properties are studied by varying the degree of crosslinking and degree of ionization systematically in the range of 1-5 and 25-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…The rheological frequency sweep confirmed the gelation state ( G ′ > G ″) of the hydrogels (Figure S2a). The incorporation of the cationic species reduced the shear and compressive modulus of the hydrogel (Figure S2a,b), which has been observed in previous studies . Hydrogel morphologies were revealed by scanning electron microscopy (SEM), and both the neutral and cationic hydrogels showed a porous network structure (Figure S3), which ensures good liquid and air permeability.…”
Section: Resultsmentioning
confidence: 99%
“…The rheological frequency sweep confirmed the gelation state ( G ′ > G ″) of the hydrogels (Figure S2a). The incorporation of the cationic species reduced the shear and compressive modulus of the hydrogel (Figure S2a,b), which has been observed in previous studies . Hydrogel morphologies were revealed by scanning electron microscopy (SEM), and both the neutral and cationic hydrogels showed a porous network structure (Figure S3), which ensures good liquid and air permeability.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate this effect, the performance of model cationic hydrogels for desalination of seawater with MFFO process has been recently investigated. [ 20 ] The results demonstrated that the swelling capacity of these hydrogels in model seawater is almost identical to that of anionic hydrogels with similar ionic strength in sodium chloride solutions. With optimized hydrogel parameters, a salt rejection of 40% from model seawater with a concentration of 11.6 g L −1 was achieved.…”
Section: Introductionmentioning
confidence: 89%
“…This approach has been experimentally and theoretically investigated in the last decade. [19][20][21][22][23][24] The overall process includes swelling and deswelling of hydrogels (see Scheme S1 in the Supporting Information). In the first step, charged hydrogels swell in a salt solution reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary to estimate the salt rejection capability of developed photothermal material, which greatly improves the long-term stability of the desalination process. The salt rejection (SR) ratio can be defined as the ratio of salt concentration (C out ) in the supernatant phase to the initial concentration of saltwater (C 0 ) [45],…”
Section: Salt Rejection Ratiomentioning
confidence: 99%